Laparoscopy In The Diagnosis Of Acute Surgical Diseases Of The Abdominal Organs (Texas Journal of Medical Science, 2026)
The article presents an analysis of the results of using diagnostic laparoscopy in 47 patients with suspected acute surgical pathology of the abdominal organs from 2020 to 2025. The author emphasizes the high informative value of the method, which allows for diagnostic verification and determination of treatment tactics with minimal trauma. Particular attention is paid to the diagnosis of acute appendicitis, including the use of the Krieger technique to identify catarrhal forms. The study proves that the implementation of laparoscopy significantly reduces the number of "unjustified" appendectomies and avoids diagnostic errors, the frequency of which reaches 30% with the traditional approach